UNIVERSAL GRAVITATION AND MAGNETISM OF THE PLANETS - E.V. Savich (Electrical engineering & Electromechanics, 2013)
The cores of the Solar System planets and the Sun are magnetized bodies, with the field of S-intensity, molten by the temperature of over million degrees. As similarly charged bodies, they interact with each other via repulsive forces that are considered, in the mechanism of gravitational attraction action, as resultant forces retaining the planets on the orbits at their inertial motion about the Sun.